Influence of the Cobalt Phase on the Highly Efficient Growth of MWNTs. (11th March 2014) - Milone, Candida; Piperopoulos, Elpida; Lanza, Maurizio; Santangelo, Saveria; Malara, Angela; Mastronardo, Emanuela; Galvagno, Signorino
In this work, the influence of the cobalt phase on the growth of carbon nanotubes by the catalytic chemical vapour deposition of CH4 with catalysts containing Co, Mo and Mg is investigated. To this end, the catalytic behaviour of physically mixed CoO/MgO+MgMoO4 and CoMoO4 +MgMoO4 is studied. The results obtained show that CoMoO4 +MgMoO4 allows for the attainment of the highest CNT yield (2407 wt % against 1296 wt %). Its higher activity is ascribed to the greater formation of active sites that, in light of current assessments, are constituted by metallic cobalt adjacent to Mo2 C, and the huge exfoliation of the catalyst, which contributes towards enhancing their exposure.